Fabrication of Bi2SiO5 hierarchical microspheres with an efficient photocatalytic performance for rhodamine B and phenol removal. (August 2019) - Dou, Lin; Zhong, Junbo; Li, Jianzhang; Luo, Jieyue; Zeng, Ying
Graphical abstract: Highlights: 3D Bi2 SiO5 hierarchical microspheres were successfully prepared. Glycerol acts as a template to guide formation of the Bi2 SiO5 hierarchical microspheres. The solvents play an important role in influencing the growth of Bi2 SiO5 . Bi2 SiO5 microspheres have better photocatalytic performance than the nanoplates. Abstract: Self-assembled three-dimensional (3D) Bi2 SiO5 microspheres were synthesized via a solvothermal method using glycerol as reaction media and NH3 H2 O as pH adjustment. The growth of Bi2 SiO5 crystal was influenced by the solvothermal time. During the preparation process, glycerol acts as a soft template to guide the formation of the hierarchical microspheres. The photocatalytic activities of Bi2 SiO5 microspheres toward the degradation of Rhodamine B and phenol under light irradiation were evaluated. Bi2 SiO5 microspheres display much higher photocatalytic activity than the Bi2 SiO5 nanoplates. The high photocatalytic activity of hierarchical Bi2 SiO5 microspheres can be ascribed to the enhanced light absorbance, the efficient separation of photo-generated electrons and holes and the large surface area. The main active species during the photocatalytic reaction are OH and O2 −, proven by terephthalic acid photoluminescence probing technique and nitroblue tetrazolium (NBT) experiments. The Bi2 SiO5 microspheres are stable during the photocatalytic reaction and can be used repeatedly.